THE STORY OF DISTURBANCE IN THE QUR’AN: A STUDY OF THE TAFSIR AL-MISHBAH BY M. QURAISH SHIHAB - Wardani, Febri; Siagian, Roihatul Jannah; Rizqi, Muhammad (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2023)
In the Qur’an, several stories tell of the turmoil of the Prophets and pious people. Humanity in general and Muslims in particular have certainly felt troubled in their lives, both because of worldly and spiritual matters. Confusion in the Qur’an occurs to a servant related to religion and belief. Meanwhile, nowadays, many things are found that lead to confusion in world affairs. This can be seen from the many confused posts about feelings of love. This research aims to analyze the stories of the Prophets and pious people who contain turmoil in the Qur’an and to provide information regarding solutions to overcome anxiety, according to M. Quraish Shihab. This research was carried out using qualitative methods; the type of research was library research, a historical approach using a bibliographic approach. The data sources used in this research consist of primary and secondary data. The primary source is the Al-Mishbah commentary book. Meanwhile, secondary sources are supporting data that make studying more accessible, such as journal articles, books, etc. Next, the interpretation is presented using Abd's thematic interpretation approach. Al-Hayy Al-Farmawī, namely, an interpretation that seeks direct answers from the Qur’an about a problem. The results of this research are that M. Quraish Shihab interprets the troubled stories of the Prophets and pious people in his tafsir with the words anxious and restless. The story of Maryam, the holy woman of tells the anxious situation. QS. Maryam [19]: 19-28, due to the influence of the accusation sentence, is the story of the Prophet Moses and the magicians. QS. T}āh{ā [20]: 57-70, which caused events carried out by witches, and the story of the Prophet Ibrahim seeking God QS. Al-An’ām [6]: 75-83 caused by human nature to want to prove the presence of God. The story that tells of a state of anxiety is the story of the Prophet Muhammad, who missed the revelation. QS. Al-Duha [93]: 1-5, which is due to allegations that Allah abandoned the Prophet and the story of Aisyah losing the necklace. QS. Al-Nūr [24]: 11-18, caused by accusations without evidence. The interpretation of troubled stories in the Al-Mishbah interpretation has causes and solutions to the troubled stories in the Qur’an. Each story has different conditions, and each trouble has its solution. Allah provides solutions to the Prophet and pious people in the Qur’an in various forms of expression. However, it is focused on one point: drawing closer to Allah and keeping away things that can damage the heart from envy and other bad qualities.